2020
DOI: 10.1038/s41416-020-0794-x
|View full text |Cite|
|
Sign up to set email alerts
|

Serine-dependent redox homeostasis regulates glioblastoma cell survival

Abstract: Background The amino acid serine is an important substrate for biosynthesis and redox homeostasis. We investigated whether glioblastoma (GBM) cells are dependent on serine for survival under conditions of the tumour microenvironment. Methods Serine availability in GBM cells was modulated pharmacologically, genetically and by adjusting serine and glycine concentrations in the culture medium. Cells were investigated for regulation of serine metabolism, proliferation, sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 57 publications
0
38
0
1
Order By: Relevance
“…Recently, the upregulation of PHGDH and SHMT2 expression under hypoxic conditions has also been observed in certain GBM cell lines. This study has shown that high levels of PHGDH protect GBM cells from hypoxia-induced cell death and starvation conditions, sustaining redox homeostasis and maintaining NADPH/NADP+ ratio [ 116 ]. Likewise, serine/glycine metabolism was previously associated with the survival of glioma tumor cells within the hypoxic areas.…”
Section: Radiotherapy Resistance and The Link With De Novo Serine/mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the upregulation of PHGDH and SHMT2 expression under hypoxic conditions has also been observed in certain GBM cell lines. This study has shown that high levels of PHGDH protect GBM cells from hypoxia-induced cell death and starvation conditions, sustaining redox homeostasis and maintaining NADPH/NADP+ ratio [ 116 ]. Likewise, serine/glycine metabolism was previously associated with the survival of glioma tumor cells within the hypoxic areas.…”
Section: Radiotherapy Resistance and The Link With De Novo Serine/mentioning
confidence: 99%
“…For instance, serine starvation resulted in reduced viability and impaired proliferation in p53-deficient tumors [ 153 ]. Inhibition of de novo serine/glycine biosynthesis is likely most effective in tumors that are reliant on de novo serine/glycine biosynthesis, such as PHGDH-amplified melanoma and breast cancers, as well as tumors with increased dependency on this pathway under metabolic/stress conditions, e.g., KRAS-mutated pancreatic tumors, which become insensitive to serine/glycine deprivation [ 16 , 26 ], or GBM and cMYC-amplified neuroblastomas with upregulation of this pathway in response to hypoxia [ 115 , 116 ]. However, it is important to consider the metabolic plasticity and the compensatory mechanisms following these therapeutic strategies.…”
Section: Future Perspectives: Therapeutic Targeting Of De Novo Sermentioning
confidence: 99%
“…For instance, Engel and colleagues reported that tumor microenvironment with high serine concentration contributed to rapid cell growth in glioblastoma. Interfering serine metabolism could be a plausible therapeutic target (Engel et al, 2020). It was reported that the proliferative ability of cancer cells could be enhanced by high content of microenvironmental serine (Labuschagne et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Saito et al reported that elevated leucine in microenvironment can promote cell proliferation in breast cancer, and induce resistance to tamoxifen (Saito et al, 2019). Engel et al found that serine content of microenvironment determined the growth and survival of glioblastoma (Engel et al, 2020). In lung cancer, the imbalance of kynurenine to tryptophan ratio in microenvironment was closely related to the resistance for immune checkpoint inhibitor (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation